Skin for Skin Death and Life for Inuit and Innu - Sider, Gerald (Duke University Press, 2014)
Since the 1960s, the Native peoples of northeastern Canada, both Inuit and Innu, have experienced epidemics of substance abuse, domestic violence, and youth suicide. Seeking to understand these transformations in the capacities of Native communities to resist cultural, economic, and political domination, Gerald M. Sider offers an ethnographic analysis of aboriginal Canadians' changing experiences of historical violence. He relates acts of communal self-destruction to colonial and postcolonial policies and practices, as well as to the end of the fur and sealskin trades. Autonomy and dignity within Native communities have eroded as individuals have been deprived of their livelihoods and treated by the state and corporations as if they were disposable. Yet Native peoples' possession of valuable resources provides them with some income and power to negotiate with state and business interests.